PENGEMBANGAN KBP DAN KEBERLANJUTAN HUTAN MANGROVE DI PATIMBAN, SUBANG, JAWA BARAT - Larasati, Sharfina Elda; Daulay, Rasoki Mintana Debara; Bashir, Imam Abdullah (Coastal and Ocean Journal (COJ), 2024)
The focus of the development of the New City of Patimban(NCP) in Subang, West Java, lies in aligning with the city's aspirations and safeguarding the nearby mangrove forests. Guided by the West Java RTRW 2022-2042 and Subang Regent Regulation No. 38 of 2021, the development faces a challenge as allocating land for industrial purposes may adversely affect the mangrove ecosystems. Examining this situation through a Social-Ecological Systems (SES) lens reveals the need to comprehend the development's impact on mangrove forests.The research, titled "The Impact of the Development of the New City of Patimban on the Sustainability of Mangrove Forests," explores the interconnectedness of economic, social, and environmental factors. The New City of Patimban contend with environmental consequences, including habitat loss, mangrove ecosystem degradation, and greenhouse gas emissions. While infrastructure development holds economic promise, it concurrently poses risks to local livelihoods. To address these challenges, the study advocates for collaboration between the government, local communities, and stakeholders to restore and protect mangrove forests. It emphasizes the importance of ongoing assessment of regulations, such as the West Java RTRW 2022-2042 and Subang Regent Regulation No. 38 of 2021, to ensure the development aligns with desired principles without compromising the environment. The article underscores the historical significance of mangrove forests in supporting the socio-economic life of fishing communities for over 150 years. It suggests leveraging mangrove forests to sustain the social and economic well-being of these communities, emphasizing the need for responsible development that preserves both urban aspirations and ecological integrity.